Plasma levels of irisin in children with idiopathic premature adrenarche - Furino, Vanessa; Furino, Fernanda; Avó, Lucimar; Melo, Débora; Germano, Carla (International Journal of Advanced Nursing Studies, 2016)
Background: Premature adrenarche (PA) is characterized by presence of isolated pubic and/or axillary hair, acne and body odor before age 8(9) in girls (boys). These individuals are at increased risk of developing insulin resistance, metabolic syndrome and polycistic ovarian syndrome. Irisin seems to have an active role in the metabolism of carbohydrates and lipids, however little is known about this hormone in PA.Objective: To analyze irisin levels in children diagnosed with PA and its relationship with their body composition.Methodology: Exploratory cross-sectional study that evaluated 15 children with PA and 15 matched controls (C). Anthropometric data were measured: height, weight, waist circumference (WC) and triceps skinfold. Fasting blood glucose(G), insulin(I), 17OHP, total cholesterol, LDL, HDL, triglycerides, DHEA-S, 25(OH)D and irisin levels were determined.Results: The levels (mean±SEM) of triglycerides [99±14, 8mg/dl (C); 68±9, 1mg/dl (AP)] and 25(OH) D [26±0, 9ng/ml(C); 30.2±1.6ng/ml (AP)] were significantly different between the groups. WC above p90 and G/ I<7 were found in 6.7% of the C group versus 33.3% and 20% of the PA group, respectively.Conclusions: PA children presented a lower G/I and a higher waist WC compared to the C group, suggesting an increased risk of metabolic disease. Irisin levels were not different between the groups. The significantly higher levels of TGs from the C group may be related to their reduced levels of 25(OH) D, which may also have masked differences in irisin levels. This study suggests that determination of vitamin D levels may be necessary to evaluate metabolic data, based on the significant frequency of this hormone insufficiency/deficiency in the pediatric population.